Pengaruh Reward Dan Job Description Terhadap Kinerja Karyawan PT. Pegadaian Syariah Cabang Pasar Ginte (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine the effect of rewards and job descriptions on the performance of PT employees. Sharia Pawnshop Ginte Market Branch. The population in this study was 30 employees, consisting of 20 permanent employees and 10 contract employees at PT. Sharia Pawnshop Ginte Market Branch. The sample in this study was 30 employees of PT. Sharia Pegadaian Pasar Ginte Branch uses a saturated sampling technique so that the entire population is used as a sample in this research. Data collection techniques use observation, questionnaires and literature study, data analysis techniques use multiple linear regression. The research results show that partially and simultaneously rewards and job descriptions have a significant effect on the performance of PT employees. Sharia Pawnshop Ginte Market Branch.